Computerized methodology for micro-CT and histological data inflation using an IVUS based translation map. (1st October 2015) - Athanasiou, Lambros S.; Rigas, George A.; Sakellarios, Antonis I.; Exarchos, Themis P.; Siogkas, Panagiotis K.; Naka, Katerina K.; Panetta, Daniele; Pelosi, Gualtiero; Vozzi, Federico; Michalis, Lampros K.; Parodi, Oberdan; Fotiadis, Dimitrios I.
Abstract: A framework for the inflation of micro-CT and histology data using intravascular ultrasound (IVUS) images, is presented. The proposed methodology consists of three steps. In the first step the micro-CT/histological images are manually co-registered with IVUS by experts using fiducial points as landmarks. In the second step the lumen of both the micro-CT/histological images and IVUS images are automatically segmented. Finally, in the third step the micro-CT/histological images are inflated by applying a transformation method on each image. The transformation method is based on the IVUS and micro-CT/histological contour difference. In order to validate the proposed image inflation methodology, plaque areas in the inflated micro-CT and histological images are compared with the ones in the IVUS images. The proposed methodology for inflating micro-CT/histological images increases the sensitivity of plaque area matching between the inflated and the IVUS images (7% and 22% in histological and micro-CT images, respectively). Highlights: A framework for inflating micro-CT/histological images is proposed. The micro-CT/histological images are transformed and validated based on IVUS. A realistic matching between IVUS and micro-CT/histological images is achieved. The overlapping plaque areas are significantly after inflation. The reliability of validation procedure is enhanced in IVUS plaque detection.